Automatic Control And Monitoring Of Greenhouse System Using Iot - et. al., Porselvi T, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents an innovative idea for controlling and monitoring the environmental conditions like temperature, soil moisture, humidity, and light intensity associated with greenhouse by using Sensor Technology and Internet of things [IoT] devices. Solar Power system is used as a renewable energy source to feed the supply to the Arduino Board via the Rechargeable battery and Solar PV Panels. A greenhouse is nothing but a glasshouse, if it has sufficient heating point or a high temperature inside the greenhouse it is termed as hot house. It is a structure in which roofs and walls made chiefly of transparent material, such as acrylic sheet, glass, plastic, fibre-glass etc., in which plants requiring regulated climatic conditions are grown. Traditional method of controlling the greenhouse parameters has the capability but it yet lacks the capability of monitoring and controlling the parameters such as light intensity, indoor humidity etc., Many farmers are unable to make decent gains from the greenhouse crops because they are unable to control two main factors, that decides both the plant production i.e., crop yield as well as its growth. The temperature inside the greenhouse should not be lower than a certain degree, high humidity can results in water vapor condensation on different greenhouse surfaces, crop transpiration and evaporation of humid soil water. So thus we are implementing, this greenhouse monitoring and automatic control system to overcome those challenges. The proposed system consists of Solar PV panels, Rechargeable battery, Adapter, Sensors to control temperature, moisture of soil, humidity and light intensity, Wireless Network, Arduino UNO. 4 channel relay board and IoT Module. The collected data from the sensors is displayed ona customized website, android app and in LCD. Thus the proposed system has the advantage, that it can be accessible anywhere and at any time.